Leadership and management policies in higher education institutions in Mexico and Costa Rica. : A binational comparative case study - Díaz Delgado, Miguel Ángel (2024)
Educational policies focused on management and leadership in higher education have gained significant importance in recent years. Decision-making, planning, organizing, and executing strategies are the responsibility of the leadership of schools, units, and faculties within various university bodies. The knowledge, skills, and competencies in management and leadership of these leaders are essential elements for implementing development strategies for research, teaching, and outreach. This study aims to compare educational leadership policies in higher education in Mexico and Costa Rica, focusing on regulations, policies, and professional development at the University of Guadalajara, the National University of Costa Rica, and the University of Costa Rica, as well as to identify a binational model. The research was conducted from a naturalistic approach with a comparative methodology, using the case study technique through document analysis. The findings conclude that the three universities are characterized by a diversity of styles and approaches in their policies, regulations, training programs, and curricula to address management and leadership, ranging from more traditional models to more participatory and collaborative approaches. They address university organization indifferent and varied ways, each with a specific logic. It was not possible to determine a binational university leadership model, nor are there institutional policies directly aimed at management and leadership for university authorities, thus opening a research avenue for future academic and interinstitutional practice.